2011
DOI: 10.1111/j.1742-4658.2011.08226.x
|View full text |Cite
|
Sign up to set email alerts
|

Muramyl‐dipeptide‐induced mitochondrial proton leak in macrophages is associated with upregulation of uncoupling protein 2 and the production of reactive oxygen and reactive nitrogen species

Abstract: The synthetic immunomodulator muramyl dipeptide (MDP) has been shown to induce, in vivo, mitochondrial proton leak. In the present work, we extended these findings to the cellular level and confirmed the effects of MDP in vitro on murine macrophages. The macrophage system was then used to analyse the mechanism of the MDP-induced mitochondrial proton leak. Our results demonstrate that the cellular levels of superoxide anion and nitric oxide were significantly elevated in response to MDP. Moreover, isolated mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…32 UCP1, UCP2, and UCP3 are thought to differ in the nature of their uncoupling activity and of their potential physiological roles. 35 Similarly, stimulation of murine macrophages by the immune modulator muramyl dipeptide rapidly upregulates the expression of UCP2, 36 and pretreatment with vitamin E attenuates upregulation of UCP2. UCP2 and 3 have been involved in a number of postulated functions in energy regulation, including regulation of insulin secretion or ROS production and control of the immune response (reviewed in Echtay).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32 UCP1, UCP2, and UCP3 are thought to differ in the nature of their uncoupling activity and of their potential physiological roles. 35 Similarly, stimulation of murine macrophages by the immune modulator muramyl dipeptide rapidly upregulates the expression of UCP2, 36 and pretreatment with vitamin E attenuates upregulation of UCP2. UCP2 and 3 have been involved in a number of postulated functions in energy regulation, including regulation of insulin secretion or ROS production and control of the immune response (reviewed in Echtay).…”
Section: Discussionmentioning
confidence: 99%
“…UCP2 mRNA has been found in several tissues including liver, brain, pancreas, adipose tissue, immune cells, spleen, kidney, and the central nervous system while UCP3 is mainly present in the skeletal muscle. 36 In addition, endothelial cells treated with Ucp2 antisense oligonucleotides 37 have been shown to present increased ROS production. 32 Although the physiological function of UCP2 is still not completely elucidated, its ability to reduce mitochondrial ROS formation is widely accepted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with previous data, we confirmed increased hepatic UCP-2 mRNA levels, 2 days after Hpx [ 97 , 98 ], however, MSC administration potentiated this expression. In the mitochondria, UCP-2 functions as an uncoupler when it is activated by superoxide and other metabolites of lipids and proteins [ 99 , 100 ]. The proton leak via UCP-2 decreases reactive oxygen species (ROS) production and protects from oxidative stress [ 101 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…UCP 2 is expressed in a number of tissues, including adipose tissues, the immune system, and pancreatic islets. [ 14 , 15 ] Several studies indicated an important role of UCP 2 in insulin/glucose homeostasis, and also demonstrated the regulation of insulin secretion by UCP 2, which possibly correlates with obesity, β-cell dysfunction, and type 2 diabetes. [ 16 , 17 ] UCP 3 expression is tissue-specific and is mostly confined to skeletal muscles, cardiac muscles, and fat tissues.…”
Section: Introductionmentioning
confidence: 99%